Safety of artemisinin-based combination therapies in Nigeria: a cohort event monitoring study (2013)
Background: A pilot programme of Cohort Event Monitoring (CEM) was conducted across the six geopolitical zones of Nigeria on patients treated for uncomplicated malaria with artemisinin-based combination therapy (ACT). The emergence and spread of malaria parasites resistant to commonly available antimalarial drugs necessitated a shift in policy for malaria treatment by the Federal Government from the use of chloroquine and sulphadoxine-pyrimethamine (SP) as first-line treatments to ACTs. Initial reports following deployment of ACTs in clinical settings raised safety concerns regarding their use. Although artemisinin and its derivatives are generally thought to be safe, there are currently few or no data on their safety among populations in Nigeria. Objectives: The main objectives of the CEM programme were to proactively determine the adverse event (AE) profile of artesunate/amodiaquine (AA) and artemether/ lumefantrine (AL) in real-life settings and to find out the factors predisposing to AEs. Methods: The CEM study was observational, longitudinal, prospective, and inceptional. Patients were observed in real-life situations. It was conducted in six public health facilities in Nigeria on patients with a clinical diagnosis of uncomplicated malaria treated with ACTs. Patients were prescribed one of the ACTs on an alternate basis as they enrolled into the programme. Follow-up reviews were undertaken on days 3 and 7 following commencement of ACT treatment. At follow-up, patients were evaluated for any clinical event that they might have experienced following the use of the ACTs. We report the result of this initial pilot in which 3,010 patients treated for uncomplicated malaria with AA or AL were enrolled. Results: The seven most common AEs seen were general body weakness 25.0/36.6 % (AL/AA); dizziness 11.9/17.2 % (AL/AA); vomiting 8.0/10.2 % (AL/AA); abdominal pain 8.5/7.2 % (AL/AA); insomnia 6.3/5.9 % (AL/AA); body pains 3.4/5.2 (AL/AA) %; anorexia 8.5/4.6 % (AL/AA). Most adverse events occurred from day 1 and peaked by day 2 and 3 of medication with the mean duration of events being 3 days. By the end of the followup visit on day 7, the AEs had resolved in the majority of patients. Adverse events were more common in the AA group than AL revealing a better safety profile for AL (p< 0.001). Both ACTs demonstrated good ability to resolve the clinical symptoms of uncomplicated malaria. Conclusion: In conclusion, this pilot CEM programme suggests that adverse events with ACTs were common. However, serious life-threatening events were not common. It appears that ACTs have a tolerable safety profile among Nigerians.